UJIAN NASIONAL: INVALID, INRELIABEL, INKONSTITUSIONAL DAN BERTENTANGAN DENGAN HAM - Takrifin, Ahmad (IAIN Pekalongan, 2009)
Since the academic year of 2003/2004, the government held the UN at the elementary and secondary education institutions. Although the UN should be carried out within the framework of the index measuring the quality of schools, in fact enable the UN has been misconstrued as a tool for determining the graduation of students. In fact, Law No.20 of 2003 on National Education System Article 58 paragraph 1 states that the assessment results of learners’ learning is done by educators only. That is, the UN has been unconstitutional. Likewise, the UN does not meet standards of validity and reliability assessment of student learning outcomes as long as six years of its implementation is not able to measure the quality of national education. In addition, the implementation of the UN in the field that gave rise to discrimination against a particular subject, and discrimination student learning outcomes, as well as a variety of fraud that have made the UN is considered contrary to human rights.